Competency-based approach to students’ training for support of children with disabilities - Larisa B. Osipova, Viktorya S. Vasilieva, Lilia A. Druzhinina, Lyubov M. Lapshina (Opción, 2019)
The article presents the analysis of the competence approach in students’ training for comprehensive maintenance of disabled children under inclusive education. The main methods are described of educational-methodical work of the pedagogical staff at the Department of Special Pedagogy, Psychology and Subject Methodology of Chelyabinsk State Pedagogical University. As a result, teaching aids are provided to the students for self-education, fulfilling individual assignments and group projects. As a conclusion, a high level of developed professional competencies allows the graduates to provide qualified correctional and developmental assistance with regard to individual psycho-physiological characteristics of all categories of children.